2020
DOI: 10.1186/s12884-020-2842-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between symptoms of depression during pregnancy and low birth weight: a prospective study

Abstract: Background: Most studies have showed that maternal depression is associated with pregnancy complications. However, there were limited evidences in Chinese population. We examined the associations of antenatal depression symptoms with pregnancy outcomes, especially for low birth weight. Methods: A total of 1377 singleton pregnant women were recruited from Nanshan Maternity & Child Healthcare Hospital of Shenzhen in this prospective cohort study. Depression symptoms were assessed by the Edinburgh postnatal depre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 29 publications
6
47
1
2
Order By: Relevance
“…It was reported that the risk of PTB in women with pre-pregnancy high BMI was significantly increased ( Baeten, Bukusi & Lambe, 2001 ; Chen, Chen & Hsu, 2020 ; Cnattingius et al, 1998 ; Cnattingius et al, 2013 ; Weiss et al, 2004 ; Zhou et al, 2019 ), whereas other studies contradicted this result, suggesting that women with a high pre-pregnancy BMI could have a protective impact on PTB ( Chen et al, 2013 ; Khashan & Kenny, 2009 ; Sebire et al, 2001 ). Furthermore, similar results have also been reported on association between pre-pregnancy BMI and LBW ( Li et al, 2020 ; Ronnenberg et al, 2003a ; Wu et al, 2020 ). However, there are relatively few studies of the effects of pre-pregnancy BMI on subsequent pregnancies for first-time mothers among Southern Chinese women.…”
Section: Introductionsupporting
confidence: 87%
“…It was reported that the risk of PTB in women with pre-pregnancy high BMI was significantly increased ( Baeten, Bukusi & Lambe, 2001 ; Chen, Chen & Hsu, 2020 ; Cnattingius et al, 1998 ; Cnattingius et al, 2013 ; Weiss et al, 2004 ; Zhou et al, 2019 ), whereas other studies contradicted this result, suggesting that women with a high pre-pregnancy BMI could have a protective impact on PTB ( Chen et al, 2013 ; Khashan & Kenny, 2009 ; Sebire et al, 2001 ). Furthermore, similar results have also been reported on association between pre-pregnancy BMI and LBW ( Li et al, 2020 ; Ronnenberg et al, 2003a ; Wu et al, 2020 ). However, there are relatively few studies of the effects of pre-pregnancy BMI on subsequent pregnancies for first-time mothers among Southern Chinese women.…”
Section: Introductionsupporting
confidence: 87%
“…It was reported that the risk of PTB in women with pre-pregnancy high BMI was significantly increased (Baeten et al 2001;Chen et al 2020;Cnattingius et al 1998;Cnattingius et al 2013;Weiss et al 2004;Zhou et al 2019), whereas other studies contradicted this result, suggesting that women with a high pre-pregnancy BMI could have a protective impact on PTB (Chen et al 2013;Khashan & Kenny 2009;Sebire et al 2001). Furthermore, similar results have also been reported on association between pre-pregnancy BMI and LBW (Li et al 2020;Ronnenberg et al 2003a;Wu et al 2020).…”
Section: Introductionmentioning
confidence: 69%
“…This may be because >10 h of MSD might be affected by maternal diseases, conditions, and behaviors, such as depression, excessive mental stress, and use of sleeping pills, 24,47,48 which may potentially decrease the neonatal birth weight. [49][50][51] Moreover, because too long MSD may have other unfavorable effects including excessive BWG, 32,33 we do not suggest that pregnant women should have >10 h of sleep.…”
Section: Discussionmentioning
confidence: 99%